Aquaculture Systems Affect the Impact of Probiotics, Prebiotics, and Synbiotics on Growth and Immunity of Oreochromis niloticus : A Systematic Review and Meta‐Analysis - Diego Cardenas Laverde; Ruth Yolanda Ruiz Pardo; Luisa Marcela Villamil Diaz (Reviews in Aquaculture, 2026)
Tilapia ( Oreochromis niloticus ) aquaculture is expanding worldwide, yet disease, environmental variability, and the need for sustainable production remain major challenges. Biotics, including probiotics, prebiotics, and synbiotics, have been explored to enhance growth and immunity, but their effectiveness across aquaculture systems is not fully understood. This systematic review and meta‐analysis examined 141 studies, including 96 with quantitative data, to identify consistent biological responses of different biotics. Probiotics were the most studied and consistently effective additives, improving weight gain, feed conversion ratio, and immune performance across diverse production environments. Synbiotics and prebiotics provided additional benefits, though less consistently. Synbiotics sometimes produced larger effects with higher variability, while prebiotics showed moderate average effects; however, the small number of available studies, substrate heterogeneity, and wide uncertainty limited confidence in their reproducibility. Immunological and biochemical analyses revealed increased lysozyme, superoxide dismutase, and catalase activities, along with reduced alanine transferase, supporting enhanced antioxidant and hepatoprotective capacity. Production system emerged as an important source of heterogeneity across studies, with closed systems displaying more consistent growth‐related responses than open systems, suggesting that the biological effects of probiotics may be system dependent. Overall, probiotics represent the most widely used and reliable strategy to enhance tilapia health and performance, while closed systems appear to provide more stable conditions for growth‐related responses. However, further research using transcriptomic approaches, such as RNA sequencing, is needed to clarify the molecular mechanisms underlying system‐dependent responses.